STEM-PjBL Model on Development of Technology Engineering Literacy and Student Learning Motivation - Beatrik Nova; Suwarma, Irma Rahma; Winarno, Nanang; Simanjuntak, Mariati Purnama (Universitas Negeri Semarang, 2024)
This meta-analysis investigates the impact of integrating Project-Based Learning (PjBL) with STEM (Science, Technology, Engineering, and Mathematics) on Technology Engineering Literacy (TEL) and student learning motivation. The study aims to provide valuable insights for educators, curriculum developers, and policymakers, guiding the design of more engaging learning experiences and supporting innovative educational practices. The research followed a systematic meta-analytic approach, including defining the research problem, setting inclusion criteria, devising a literature search strategy, selecting studies, extracting data, performing statistical analysis, and interpreting results. Analyzing 33 articles from international and national journals, the study reveals that PjBL-STEM significantly enhances TEL, particularly at the high school and college levels, and boosts student motivation, with more pronounced effects observed in high school and college compared to junior high and elementary schools. The model shows a strong impact on TEL in Physics but has lower effects in Science and Biology. For student motivation, significant improvements are noted in Science, Mathematics, and Social Sciences, while effects are less in Chemistry and Physics. The research highlights the effectiveness of PjBL-STEM at higher educational levels and underscores its potential to improve TEL and motivation, though further research is needed to refine adaptation strategies for different educational contexts.